2020
DOI: 10.3390/molecules25081891
|View full text |Cite
|
Sign up to set email alerts
|

First-Principles Study of Nitrogen Adsorption and Dissociation on PuH2 (111) Surface

Abstract: Plutonium mononitride is one of the main fuels for Generation IV reactors and can be prepared from nitrogenation of plutonium hydride. We investigated the adsorption and dissociation of nitrogen on PuH2 (111) surface to elaborate the initial stage of nitrogenation. The adsorption energies varied greatly with respect to the adsorption sites and orientations of the adsorbed molecule. The nitrogen exhibited preferential adsorption above the ccp site, where the molecular nitrogen was nearly parallel to the PuH2 su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Rani and Dharamvir 34 reported N–N repulsions for nitrogen adsorption on graphene sheets. Wang et al 35 compared the nitrogen adsorption energies of the two ccp-hcp sites on plutonium hydride and observed that the nitrogen atom exhibited slightly less preferred adsorption at the ortho hcp site. They interpreted this relationship by the repulsion of the two nitrogen atoms on the surface of the material.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rani and Dharamvir 34 reported N–N repulsions for nitrogen adsorption on graphene sheets. Wang et al 35 compared the nitrogen adsorption energies of the two ccp-hcp sites on plutonium hydride and observed that the nitrogen atom exhibited slightly less preferred adsorption at the ortho hcp site. They interpreted this relationship by the repulsion of the two nitrogen atoms on the surface of the material.…”
Section: Resultsmentioning
confidence: 99%
“…Though nitrogen adsorption also equally determines the adsorption selectivity and overall performance of the adsorbents. The role of acid–base interactions and the effect of the N-hetero atom on the adsorption behavior of adsorbents have been extensively reported in the literature. , , However, very few reports are available regarding the N–N interaction between N-adsorbate and nitrogen molecules; a more detailed investigation is required to investigate the role of N–N interactions. In the present manuscript, we discussed both carbon dioxide and nitrogen adsorption, considering possible electrostatic interactions like acid–base interaction and N–N repulsion with the textural properties of the material.…”
Section: Introductionmentioning
confidence: 99%